Analysis of the work rates and heart rates of association football referees. Issue 3 (September 1993) - Catterall, C; Reilly, T; Atkinson, G; Coldwells, A
Abstract : This study aimed to describe the work-rate profiles of referees during soccer matches and record heart-rate responses during these games. Using video-recordings 14 referees were observed and their heart rates during the games were monitored by short-range radio telemetry. These included 11 football league matches. The exercise intensity was largely submaximal with a change in activity every 6 s. The mean distance covered during the game was 9.44 km; a significant fall in work rate was noted in the second half (P < 0.05). The mean heart rate of 165 beats min-1 did not vary between first and second halves. The work rate and heart rate varied more between individuals than with the importance of the match, but this variation was small. It was considered that refereeing top level soccer places high physiological demands on the official. This has implications for training and fitness assessment.